Application of starter cultures to table olive fermentation: an overview on the experimental studies - Corsetti, Aldo; Perpetuini, Giorgia; Schirone, Maria; Tofalo, Rosanna; Suzzi, Giovanna (Frontiers in Microbiology, 2012)
Table olives are one of the oldest fermented foods and are considered as an important component of the Mediterranean diet, since their richness in monounsaturated fats (primarily oleic acid) and phenolic compounds may function as antioxidants in the human body; in the Western world they represent one of the most popular fermented vegetables but, despite its economic significance, table olive fermentation is still craft-based and empirical. In particular, such a type of fermentation results from the competitive activities among indigenous, contaminating microorganisms, the microbial balance depending on several intrinsic (pH, water activity, diffusion of nutrients from the drupe, and level of anti-microbial compounds) and extrinsic (temperature, oxygen availability, and salt concentration) factors. At present, to reduce the risk of spoilage and to achieve a more predictable process there is an increasing interest in developing starter cultures for table olives fermentation. Anyway, the application of starter cultures in the field of table olives is quite far from reaching the diffusion as it has in other sectors of food industry (e.g., dairy products and alcoholic beverages). This review focuses on experimental researches devoted to studying starter cultures for possible application to table olive fermentation both at artisan and industrial level.